2003
DOI: 10.1001/jama.290.11.1479
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Childhood Distal Forearm Fractures Over 30 Years

Abstract: REVIOUS STUDIES HAVE SHOWNthat the incidence of distal forearm fractures in children peaks during early adolescence around the time of the pubertal growth spurt. [1][2][3] This observation has been explained on the basis of a transient increase in cortical porosity that results from enhanced bone turnover in response to greater calcium demand at the time of maximal longitudinal bone growth. 4 Such a process might be especially problematic given the thin cortex of the metaphyseal region of the distal radius, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
290
1
21

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(347 citation statements)
references
References 39 publications
28
290
1
21
Order By: Relevance
“…(6,7,9,14,(28)(29)(30) None of the anatomic sites alone was responsible for the decrease in overall incidence but was most pronounced in hand and foot fractures. The surprising increase in the incidence of forearm and upper arm fractures is parallel to reports from the United States and Japan (11,12) and in line with a recent Finnish registry-based nationwide study on operatively treated fractures between 1997 and 2006. (19) A similar increase in forearm fractures also was seen in Sweden from 1975 to 1994 in girls (15) but not in boys.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…(6,7,9,14,(28)(29)(30) None of the anatomic sites alone was responsible for the decrease in overall incidence but was most pronounced in hand and foot fractures. The surprising increase in the incidence of forearm and upper arm fractures is parallel to reports from the United States and Japan (11,12) and in line with a recent Finnish registry-based nationwide study on operatively treated fractures between 1997 and 2006. (19) A similar increase in forearm fractures also was seen in Sweden from 1975 to 1994 in girls (15) but not in boys.…”
Section: Discussionsupporting
confidence: 73%
“…(1,(5)(6)(7) The pattern of fractures varies between countries and even regions within a country, depending on local climate, culture, and leisure-time activities. (7)(8)(9)(10) Some studies have shown an increasing incidence of pediatric fractures at specific sites, (11,12) but population-based data on overall pattern and epidemiologic trends of childhood fractures are scarce. (13) In Sweden, the incidence of childhood fractures, especially of those caused by low-energy trauma, almost doubled from the 1950s to 1970s, (1,14) reaching an incidence of 212 fractures per 10,000 population.…”
Section: Introductionmentioning
confidence: 99%
“…В скобках -% детей с недостаточным потреблением кальция. увеличение числа зарегистриро-ванных случаев переломов костей предплечья в когорте лиц младше 35 лет приходилось на возраст 11-14 лет у мальчиков (у 11-15% в год) и 8-11 лет у девочек (у 8-12% в год) [18]. По результатам изучения анало-гичной проблемы J. Konstantynowicz и соавт., именно это обстоятельство стало определяющим для четырех-кратного увеличение риска перелома костей у девочек, но не у мальчиков [19].…”
Section: пищевые дефициты и их влияние на состояние опорно-двигательнunclassified
“…В связи с этим важно отметить, что в США за период с 1977-1978 по 1994-1996 гг. произошло снижение потребления молока девочками старшего школьного возраста почти на 2/3 на фоне поч-ти двукратного увеличения потребления неалкогольных напитков [18].…”
Section: пищевые дефициты и их влияние на состояние опорно-двигательнunclassified
“…Despite the growing body of published normative data utilizing DXA in children, there are no evidence-based guidelines for the definition of osteoporosis in children. Fractures occur commonly in otherwise healthy children, with a peak incidence during early adolescence around the time of the pubertal growth spurt [34]. Several studies have compared the DXA BMD of normal children and adolescents with forearm fractures to that of age-matched controls without fractures.…”
Section: Skeletal Modeling During Growth and Developmentmentioning
confidence: 99%